Relationship-Rich Education : How Human Connections Drive Success in College - Felten, Peter; Lambert, Leo M., 1955- (Book collections on Project MUSE., 2020)
"The coauthors argue that the best undergraduate education is one that brings students into sustained relationships with peers, faculty, staff, and other mentors. The coauthors illustrate that relationship-rich environments can and do exist for students at all types of institutions, not just elite ones. Students learn best in an environment of high expectation and high support, and all faculty and staff can learn to teach and work in ways that enable relationship-based education"--